2009
DOI: 10.2109/jcersj2.117.157
|View full text |Cite
|
Sign up to set email alerts
|

Nitridation behaviour of ZrO2 added silicon powder with different ZrO2 particle sizes

Abstract: Effect of zirconia particle size on the nitridation behavior of silicon powder was studied in order to assess the influence of the zirconia particle size on the nitridation of silicon powder. Thermo-gravimetric analysis revealed that for samples held at higher temperatures the addition of zirconia powder resulted in a reduction of the temperature for the onset of nitridation of the silicon powder, and the degree of silicon to silicon nitride conversion at a given temperature was higher for samples nitrided wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…On the other hand, in the case of the SiAlON powder with ZrO 2 additions, the starting temperature of the main weight gain step occurring around 13001C was clearly lower than those for the other powders. 19,20 (2) Reaction Bonding and Postsintering Figure 3 shows the photographic images of the reaction-bonded SiAlON samples with and without ZrO 2 as a function of differ- Fig. 17 Figure 2 shows the normalized degree of nitridation, calculated from the TG analysis results, for mixed powders corresponding to the SiAlON composition of Z 5 1 with and without ZrO 2 that were heated and then held at 14001C under flowing nitrogen conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the case of the SiAlON powder with ZrO 2 additions, the starting temperature of the main weight gain step occurring around 13001C was clearly lower than those for the other powders. 19,20 (2) Reaction Bonding and Postsintering Figure 3 shows the photographic images of the reaction-bonded SiAlON samples with and without ZrO 2 as a function of differ- Fig. 17 Figure 2 shows the normalized degree of nitridation, calculated from the TG analysis results, for mixed powders corresponding to the SiAlON composition of Z 5 1 with and without ZrO 2 that were heated and then held at 14001C under flowing nitrogen conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This nitridation-enhancing mechanisms has been reported by the authors in detail. 19,20 (2) Reaction Bonding and Postsintering Figure 3 shows the photographic images of the reaction-bonded SiAlON samples with and without ZrO 2 as a function of differ- Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…The sintered reaction-bonded Si 3 N 4 has been considered as a more attractive alternative, due to the low cost of Si powders and low sintering shrinkage. [7][8][9] Results showed that all of the oxides exhibited nitridation enhancing effect. To overcome this problem, many researchers have reported the catalytic nitridation of Si.…”
Section: Introductionmentioning
confidence: 99%
“…1 The fabricating cost of Si 3 N 4 ceramics is the main barrier in sintering of Si 3 N 4 powder because of the high cost of raw materials as well as post-machining process. [5][6][7][8][9] Hyuga et al studied the effect of oxides additives including ZrO 2 plus 16 kinds of rare earth oxides on nitridation of Si powders. [2][3][4] However, the application of sintered reaction-bonded Si 3 N 4 ceramics is limited by the long processing time such as slow nitridation of Si powders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation